Community policing and human security in Nigeria: a study of Lagos State Neighbourhood Safety Corps (LNSC) / Abdul Rauf Ambali and Akeem Ayanda Araba - Araba, Akeem Ayanda; Ambali, Abdul Rauf (Universiti Teknologi MARA, 2020)
The need to examine the problem of crime that has become a recurring feature in all states in Nigeria necessitates this study. There is no doubt that community policing has been very effective in crime reduction and control in several countries including the US, Israel, UK, Canada, and Japan. The devastating impacts in the face of apparently soaring levels of crime and violence on Nigerian individuals and communities especially in Lagos and other states in Nigeria require quick action. The need for community policing is critical to identifying those who are planning to carry out acts of violence. The objectives of the study are to i) ascertain the extent to which Neighbourhood Safety Corps is equipped and empowered to provide security to Lagosian; ii) investigate whether the establishments of Neighbourhood Safety Corps have reduced the rate of crime rate and improve human security in Lagos State. The paper employs a primary and secondary source of collecting data. Descriptive statistics and correlational analysis were used to analysed data and test the null hypotheses at 0.05 levels of significance. The study adopts the Normative Sponsorship Theory for its analysis. The study reveals that the provision of adequate equipment to community personal enhances the security of lives and properties. More so, the creation of community policing to support the government apparatus reduced the crime rate in any society. Based on the findings of this paper, it was recommended that government should redouble its efforts in providing sophisticated weapons and ammunition to the community policing personnel and also should encourage the establishment of partnership policing to curb the crime rate